Assessing Equitable Adherence to the Age-Friendly Health System's 4Ms Framework in an Academic Inpatient Setting - Julia Adler-Milstein PhD; Robert Thombley BS; Sarah Rosenthal BA; Benjamin Rosner MD, PhD; Stephanie Rogers MD (SAGE Publishing, 2024)
While thousands of health systems have begun to implement the Age-Friendly Health System's 4Ms Framework to improve care for older patients, an important phase of work is achieving consistent adherence to 4Ms care processes. Identifying mechanisms that may lead to higher versus lower adherence serves to guide efforts to achieve consistent, equitable adherence. Drawing from prior literature, we identified three mechanisms that may influence 4Ms adherence. We then conducted a 3-year retrospective, observational study of inpatient encounters (n = 28 833) at UCSF Health System with patients aged 65+. We used least squares regression models to assess associations between hospital encounter-level measures of 4Ms adherence and proxy measures of patient and encounter characteristics for each hypothesized mechanism along with control variables. Encounter-level adherence to the 4Ms was 65.5% (SD = 14.3%). We found support for all three mechanisms. Negative implicit biases were associated with lower adherence for patients who were obese [0.79 percentage points (PP) lower; P  < .001] or on Medicaid (0.64 PP lower; P  = .002). Positive implicit biases were associated with higher adherence for the oldest old (aged 85+; 2.85 PP higher; P  < .001) or with reduced mobility (2.01 PP higher; P  < .001). Patients with comprehensive geriatrics care contact (ACE unit and a geriatrics consult) had 5.33 PP higher adherence ( P  < .001). While most effects were modest in magnitude, our results suggest that both positive and negative implicit biases, as perceived by the provider, may influence the level of 4Ms adherence. Contact with comprehensive geriatrics care appeared most influential. These insights can be leveraged to develop strategies to achieve equitable delivery of 4Ms care.